2002
DOI: 10.1074/jbc.m202037200
|View full text |Cite
|
Sign up to set email alerts
|

Mice Deficient in the Insulin-regulated Membrane Aminopeptidase Show Substantial Decreases in Glucose Transporter GLUT4 Levels but Maintain Normal Glucose Homeostasis

Abstract: The insulin-regulated aminopeptidase (IRAP) is a zincdependent membrane aminopeptidase. It is the homologue of the human placental leucine aminopeptidase. In fat and muscle cells, IRAP colocalizes with the insulin-responsive glucose transporter GLUT4 in intracellular vesicles and redistributes to the cell surface in response to insulin, as GLUT4 does. To address the question of the physiological function of IRAP, we generated mice with a targeted disruption of the IRAP gene (IRAP؊/؊). Herein, we describe the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
98
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 69 publications
8
98
0
5
Order By: Relevance
“…We furthermore provide correlative evidence (r 2 ϭ 0.47, P ϭ 0.05) that training-induced changes in GLUT4 protein occur in coordination with changes in protein expression of IRAP. This finding is supported by a previous cross-sectional human study (55) and suggests that also in human muscle IRAP is not only a marker of GLUT4-containing vesicles but also may be directly involved in maintaining GLUT4 expression and vesicle trafficking (28,56). In the present study, an ϳ200% increase in the protein content of HK2 was observed.…”
supporting
confidence: 80%
“…We furthermore provide correlative evidence (r 2 ϭ 0.47, P ϭ 0.05) that training-induced changes in GLUT4 protein occur in coordination with changes in protein expression of IRAP. This finding is supported by a previous cross-sectional human study (55) and suggests that also in human muscle IRAP is not only a marker of GLUT4-containing vesicles but also may be directly involved in maintaining GLUT4 expression and vesicle trafficking (28,56). In the present study, an ϳ200% increase in the protein content of HK2 was observed.…”
supporting
confidence: 80%
“…Interestingly, Glut4 Ϫ/Ϫ mice (similar to our Tnks2 PARP-deleted mice) display growth retardation and are 20% smaller than controls (31). However, since IRAP Ϫ/Ϫ mice do not have decreased body weight (33), the role of the IRAP-tankyrase 2 interaction in the small mouse phenotype remains to be determined.…”
Section: Discussionmentioning
confidence: 97%
“…After insulin stimulation, both IRAP and GLUT4 translocate from vesicles in the cytoplasm and trans-Golgi network to the plasma membrane (reviewed in reference 32). In IRAP Ϫ/Ϫ mice, absence of IRAP resulted in decreased GLUT4 expression (33). It has been suggested that tankyrases 1 and 2 may have a role in targeting or maintenance of GLUT4 vesicles (11,50).…”
Section: Discussionmentioning
confidence: 99%
“…IRAP null mice exhibit apparently normal GLUT4 translocation (Keller et al, 2002), indicating, as expected, that the cytoplasmic domains of GLUT4 possess the information requisite for proper GSV trafficking. Indeed and as noted above, dileucine and acidic cluster sequences in IRAP's N-terminus are very similar to those in the GLUT4 C-terminus.…”
Section: Molecular Biology Of the Cell 2888mentioning
confidence: 91%